2012
DOI: 10.1111/j.1469-7610.2012.02599.x
|View full text |Cite
|
Sign up to set email alerts
|

Links between infant temperament and neurophysiological measures of attention to happy and fearful faces

Abstract: The peak latency of the Nc was slower for infants with lower regulatory capacity, independent of facial expression. The amplitude of the Nc over right fronto-central electrodes was related to both self-regulation and negative emotionality, but the effects differed by emotion: infants with better self-regulation had larger Nc responses to fearful faces, and infants scoring higher on negative emotionality had larger Nc responses to happy faces. These results are discussed in relation to the development of execut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 44 publications
7
48
2
Order By: Relevance
“…Although we expected IBQ-R subscales representing negative emotionality to be related to infants' ERP responses to negative facial expressions, no associations between these measures were found. Our results are similar to the findings by Martinos and colleagues [57] showing that only infants' self-regulation abilities but not infants' negative emotionality per se was associated with infants' ERP responses to negative (fearful) emotional expressions. In line with our findings, Martinos and colleagues [57] showed that infants that were better at self-regulation showed a larger Nc response to fearful facial expressions.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although we expected IBQ-R subscales representing negative emotionality to be related to infants' ERP responses to negative facial expressions, no associations between these measures were found. Our results are similar to the findings by Martinos and colleagues [57] showing that only infants' self-regulation abilities but not infants' negative emotionality per se was associated with infants' ERP responses to negative (fearful) emotional expressions. In line with our findings, Martinos and colleagues [57] showed that infants that were better at self-regulation showed a larger Nc response to fearful facial expressions.…”
Section: Discussionsupporting
confidence: 92%
“…The IBQ-R consists of 14 subscales that cover a wide range of temperamental traits: approach, vocal reactivity, high intensity pleasure, smiling and laughter, activity level, perceptual sensitivity, sadness, distress to limitations, fear, falling reactivity/rate of recovery from distress, low intensity pleasure, cuddliness, duration of orienting, soothability [72]. In accordance with previous studies that investigated the influence of temperament on infants perception of emotions and frontal EEG alpha asymmetry [57], [58], temperament analyses in the present study were limited to two dimensions of infant temperament, namely, ‘negative emotionality’ (as indexed by the subscales fear, sadness, distress to limitations, recovery from distress) and approach oriented temperament (as indexed by the subscales approach and duration of orienting).…”
Section: Methodssupporting
confidence: 62%
See 1 more Smart Citation
“…The Nc is thought to reflect the orienting of processing resources to attention-grabbing stimuli (de Haan & Matheson, 2009). Thus, the appearance of the Nc is thought to reflect automatic attention processes, while the modulation of Nc amplitude reflects more controlled application of sustained attention (Martinos et al, 2012). The orienting and modulation marked by the Nc is subserved by the anterior cingulate cortex (ACC), which is in turn thought to regulate limbic activity (de Haan, Johnson, & Halit, 2003; Peltola, Leppanen, Maki, et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, infants' neural sensitivity to emotional expressions is robustly associated with individual differences in temperamental traits (Martinos, Matheson, & de Haan, ; Ravicz, Perdue, Westerlund, Vanderwert, & Nelson, ; Taylor‐Colls & Fearon, ). For example, de Haan and colleagues () reported that being higher on fearfulness on the Infant Behavior Questionnaire (IBQ‐R; Gartstein & Rothbart, ) at 7 months is related to a larger Nc to static fearful faces.…”
Section: Introductionmentioning
confidence: 99%